ENDOGAMY, CONSANGUINITY AND THE HEALTH IMPLICATIONS OF CHANGING MARITAL CHOICES IN THE UK PAKISTANI COMMUNITY. Issue 4 (30th August 2016) - Small, Neil; Bittles, Alan H.; Petherick, Emily S.; Wright, John
Summary: The biraderi (brotherhood) is a long-established, widely prevalent dimension of social stratification in Pakistani communities worldwide. Alongside consanguinity, it offers a route for cementing social solidarities and so has strong socio-biological significance. A detailed breakdown of biraderi affiliation among participants in an ongoing birth cohort study in the northern English city of Bradford is presented. There is historical resilience of intra- biraderi marriage, but with a secular decline in prevalence across all biraderi and considerable reductions in some. While a majority of marriages in all biraderi are consanguineous the prevalence varies, ranging from over 80% to under 60%. In consanguineous unions, first cousin marriages account for more than 50% in five of the fifteen biraderi and >40% in six others. Within- biraderi marriage and consanguinity enhance genetic stratification, thereby increasing rates of genomic homozygosity and the increased expression of recessive genetic disorders. The trends reported constitute putative signals of generational change in the marital choices in this community.